Problems of Allocation of Consumer Loans in Commercial Banks (European Journal of Economics, Finance and Business Development, 2024)
This article examines the complexities and challenges associated with the allocation of consumer loans within commercial banks. By analyzing the literature, it examines the methods used, the results obtained, and discusses the implications. Conclusions from the discussion provide insights and suggestions for addressing these issues.